Nanomedicines for Delivery of Cytarabine: Effect of Carrier Structure and Spacer on the Anti-Lymphoma Efficacy - Pola, Robert; Grosmanová, Eliška; Pechar, Michal; Kostka, Libor; Pokorná, Eva; Tušková, Liliana; Klener, Pavel; Etrych, Tomáš (Polymers, 2025)
High-dose therapy with cytarabine (araC) is a standard treatment for aggressive non-Hodgkin lymphomas, but its efficacy is limited by rapid enzymatic degradation. To overcome this, araC was conjugated to N-(2-hydroxypropyl)methacrylamide (HPMA) copolymers to form linear and star-like nanomedicines using six different spacers: 3-aminopropanoyl, 5-pentanoyl, 6-aminohexanoyl, 4-aminobenzoyl, glycyl, and diglycyl. The conjugates contained 12.5-14.7 wt% araC and exhibited distinct hydrolytic release profiles at pH 7.4. LC1 (3-aminopropanoyl) and LC6 (diglycyl) released the drug most rapidly (~80% bound after 72 h), and LC2, LC3, and the star conjugate SC1 showed intermediate stability (~90%), while LC4 (4-aminobenzoyl) was most stable (~95%). In vivo, all conjugates markedly suppressed tumor growth in patient-derived xenograft models of mantle cell and Burkitt lymphoma compared with free araC. LC1 and LC2 provided the most durable tumor control, delaying regrowth beyond 40 days, and SC1 achieved comparable efficacy at a reduced araC-equivalent dose (2 mg/mouse vs. 3 mg/mouse for linear conjugates). These results demonstrate that spacer structure critically influences drug release and identify LC1 and LC2 as promising candidates for further development in lymphoma therapy.
Keywords: nanotherapeutics; HPMA copolymer; cytarabine; mantle cell lymphoma; drug delivery